Citizens Party (U.S.) records - Citizens Party (U.S.)
Correspondence, meeting notes, financial records, membership directories, newsletters, newspaper clippings, and printed matter pertaining to the organization of the Citizens Party at the national and local level, the formation of its platform, and its campaign efforts. Documents the campaign of Barry Commoner and LaDonna Harris as the party's candidates in the 1980 presidential election.
Political party composed of environmentalist and liberal groups. Formed in 1979; dissolved in 1987.
Collection material in English.
Keywords: Environmentalism -- United States; Liberalism -- United States; Political parties -- United States; Presidents -- United States -- Election -- 1980.; United States -- Politics and government -- 1945-1989.